2012
DOI: 10.1016/j.physbeh.2011.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of chow and purified diet on the consumption of sucrose solution and lard and the development of obesity

Abstract: Obesity has been associated with increased consumption of sweetened beverages and a high-fat diet. We determined whether the composition of the dry pellet offered with liquid sucrose (LS) and lard influenced the development of obesity. We hypothesized that animals offered LS or LS and lard (choice), in addition to chow or purified low fat diet pellet (LFD; 10% fat), would gain more body fat than controls. We compared the effects of LFD vs. chow on voluntary consumption of LS and lard, serum triglyceride (TG), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 24 publications
2
26
1
Order By: Relevance
“…The difference in body weight is why controls groups are necessary for every experiment. It should be noted that the previous study (Apolzan & Harris, 2012) and in the present study no differences in lean body mass were shown. The lack of a body weight response suggests it is critical to measure body composition to determine if body fat differences are present.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…The difference in body weight is why controls groups are necessary for every experiment. It should be noted that the previous study (Apolzan & Harris, 2012) and in the present study no differences in lean body mass were shown. The lack of a body weight response suggests it is critical to measure body composition to determine if body fat differences are present.…”
Section: Discussioncontrasting
confidence: 48%
“…In experiments 2 & 3 the body weights were not different between the groups. Also, in the original paper examining the choice model, there were no difference in body weight or body weight gain between the choice and chow groups over 21 days (Apolzan & Harris, 2012). However, in Harris and Apolzan (Harris & Apolzan, 2012) choice were heavier than chow rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that rats offered choice diet rapidly become obese and glucose intolerant (4,35,36). The objective of the first study described here was to determine whether glucose intolerance, obesity, and leptin resistance developed faster in rats offered choice diet than in those fed a composite HFD and whether this was associated with consumption of lard or of sucrose solution.…”
Section: Discussionmentioning
confidence: 97%
“…Purified diet, however, is kept constant, and is therefore usually preferred. There have been reports that feeding experimental animals laboratory chow versus a purified diet can yield markedly different results4243. For this reason, we compared db/+ and WT mice fed a standard chow diet in addition to the purified diet used in Study 1, to determine if this would unmask the GDM phenotype.…”
Section: Discussionmentioning
confidence: 99%